Non-Marital Abusive Relationships: A Criminal Law Perspective - Larissa, Dea; Yoga Saputra; Hasnan Hasbi (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
Abusive relationships represent a form of interpersonal association characterized by recurrent acts of physical, psychological, sexual, or economic coercion exercised by one partner over another. From the standpoint of criminal jurisprudence, such conduct not only infringes upon the victim’s inherent dignity and autonomy but also constitutes a culpable act punishable under the prevailing criminal law framework. This article seeks to undertake a doctrinal examination of the criminal law dimensions governing abusive relationships by analyzing the constituent elements of the offense, the interpretive application of relevant provisions of the Indonesian Criminal Code, and the practical constraints encountered in their enforcement. Employing a normative juridical method, the research engages in a critical appraisal of statutory instruments and judicial precedents pertinent to acts of intimate partner violence. The findings demonstrate that, notwithstanding the promulgation of legal frameworks such as the Domestic Violence Elimination Act (PKDRT Act), significant impediments persist, particularly in evidentiary substantiation, societal stigmatization, and the limited juridical competence of law enforcement officials. Accordingly, the study argues for the consolidation of victim-centered legal protections and the refinement of prosecutorial and judicial practices, thereby fostering a more coherent and human-rights–oriented approach to the criminalization and adjudication of abuse within non-marital relationships.